A study on stryi-icnos potatorum and pisum sativum as natural coagulants for meat food processing wastewater - Pahazri, Nor Fadzilah (2018)
Slow maintained load test is widely used by contractors in Malaysia to ensure the driven pile could accommodate the design load of the structure. Slow maintained load test is a test to determine load-settlement curve and pile capacity for a period of time using conventional load test. Conventional static pile load test equipment is large in size thus making it heavier and takes a long time to install. In addition, it consumes a lot of space which causes congestion at construction sites. Therefore, the objective of this thesis is to conduct a conventional load test by replacing the pile kentledge load with anchorage and reaction pile. Preparations of ten designs comprising six commercial designs were reviewed. In addition, four proposed designs were suggested for the setup. Final design was produced based on its safety factors and criteria referred via literature review. The test frame consists of reaction frame with four reaction helical pile with two helixes per reaction pile. The deformation shapes, safety factor, stress, and strain of the design and finite element of the model has been analysed with the use of SolidWorks and Pia.xis 30 software. SolidWorks software emphasizes on the model load-deflection relationship while Plaxis 30 ensures a correlation of reaction between pile uplift force and soil. Then, the model was tested on site to determine the relationship between physical loaddeflection and pile-soil uplift force. The results of uplift force and displacement for numerical and physical test were nearly identical which increment of loaddisplacement graph pattern. The higher the uplift force, the higher the displacement obtained. In conclusion, the result obtained and the design may be considered as a guideline for future application of sustainable slow maintained pile load test.